The Urgency of Restorative Justice Regarding Customary Criminal Violations: Harmonization Between Customary and National Criminal Laws - Bintara Sura Priambada (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Indonesia is rich in cultural and traditional diversity, including a variety of customary laws in different regions. Conflict often arises between customary laws and national criminal laws. Restorative Justice is an important approach to resolving this conflict, with a focus on reconciliation rather than punishment. This research aims to understand the implementation of Restorative Justice in the Indonesian context, identify its positive and negative impacts, and contribute valuable insights to international discussions on legal conflicts in culturally diverse societies. Normative legal research methods and document analysis are used for this study. The findings suggest that the implementation of Restorative Justice in resolving violations of customary criminal laws in Indonesia has the potential to enhance harmony between customary and national criminal laws. Necessary steps include establishing a dedicated restorative justice judicial system, involving local communities, fostering collaboration between authorities of customary and national criminal laws, and conducting extensive public education. However, it is crucial to consider both the positive outcomes, such as community relationship restoration and reduced burdens on the criminal justice system, and the negative impacts, including potential justice disparities and implementation challenges. Therefore, the integration of restorative justice needs to be carefully aligned with principles of justice, respect for customary culture, and the protection of the rights of vulnerable victims and offenders.